Efficient and Non-genotoxic RNA-Based Engineering of Human T Cells Using Tumor-Specific T Cell Receptors With Minimal TCR Mispairing - Campillo-Davo, Diana; Fujiki, Fumihiro; Van den Bergh, Johan M. J.; De Reu, Hans; Smits, Evelien L. J. M.; Goossens, Herman; Sugiyama, Haruo; Lion, Eva; Berneman, Zwi N.; Van Tendeloo, Viggo (Frontiers in Immunology, 2018)
Genetic engineering of T cells with tumor specific T-cell receptors (TCR) is a promising strategy to redirect their specificity against cancer cells in adoptive T cell therapy protocols. Most studies are exploiting integrating retro- or lentiviral vectors to permanently introduce the therapeutic TCR, which can pose serious safety issues when treatment-related toxicities would occur. Therefore, we developed a versatile, non genotoxic transfection method for human unstimulated CD8+ T cells. We describe an optimized double sequential electroporation platform whereby Dicer substrate small interfering RNAs (DsiRNA) are first introduced to suppress endogenous TCR α and β expression, followed by electroporation with DsiRNA-resistant tumor-specific TCR mRNA. We demonstrate that sequential double electroporation of human primary unstimulated T cells with DsiRNA and TCR mRNA leads to unprecedented levels of transgene TCR expression due to a strongly reduced degree of TCR mispairing. Importantly, superior transgenic TCR expression boosts epitope-specific CD8+ T cell activation and killing activity. Altogether, DsiRNA and TCR mRNA sequential double electroporation is a rapid, non integrating and highly efficient approach with an enhanced biosafety profile to engineer T cells with antigen-specific TCRs for use in early phase clinical trials.